Phosphorus dynamics in the water of tropical semiarid reservoirs in a prolonged drought period - Becker, Vanessa (2018)
Aim: To verify the vertical distribution of phosphorus in the water and to identify the predominant forms of P in the water column for understand the phosphorus dynamics in tropical semiarid reservoirs during a prolonged drought period. Methods: Two reservoirs from the semiarid region of Rio Grande do Norte were analysed during the period from May 2015 to June 2016. Were analysed: Suspended solids (SS), chlorophyll a (Chl-a), dissolved oxygen (OD) and temperature. Vertical profiles were plotted for total phosphorus (PT), total dissolved phosphorus (PTD), particulate phosphorus (PP), dissolved organic phosphorus (POD) and soluble reactive phosphorus (FRS). Results: The phosphorus values distributed in the water column were high for both reservoirs, presenting the highest values during the periods with lower depth. Gargalheiras presented greater predominance of PT and PP, while Cruzeta had the highest values of FRS. Chl-a and SS values were also consistent with phosphorus values: Chl-a was higher in Gargalheiras, while SS, mainly inorganic, were higher in Cruzeta. Gargalheiras presented anoxic conditions close to the sediment from May 2015 to December 2015, which may induce the release of phosphorus from the sediment to the water column. Values that are too high during the shallower months, especially in Cruzeta, may have been influenced by the release of P from sediment through wind resuspension. Conclusions: The amounts and predominant types of phosphorus in the water column are of great importance to understand the phosphorus dynamics and will support restoration plans for the studied environments. In this study it was possible to verify that the reservoirs are susceptible to the release of P from the sediment due to the environmental conditions, mainly low depths, resuspension of the wind and anoxia in the hypolimnion